Anxiety, Depression, and Satisfaction With Life Among College Students in China: Nine Months After Initiation of the Outbreak of COVID-19 - Xiao, Pei; Chen, Liang; Dong, Xiaoqin; Zhao, Zhiya; Yu, Jincong; Wang, Dongming; Li, Wenzhen (Frontiers in Psychiatry, 2022)
Background/Objective Mental health problems are common among college students. This study sought to assess the prevalence and risk factors of depressive and anxiety symptoms and well-being among Chinese college students 9 months after initiation of the outbreak of COVID-19. Method A cross-sectional study (N = 3,951, mean age = 19.58) was conducted from October to December 2020. An online survey was used to collect socio-demographic data, and the symptoms of depression and anxiety and satisfaction with life using Disorder 7-Item Scale (GAD-7), the Patient Health Questionnaire 9-Item Scale (PHQ-9), and the 5-items Satisfaction with Life Scale (SWLS). Results The prevalence of depressive and anxiety symptoms was 59.35 and 54.34%, respectively, and the score of satisfaction with life was 20.51 ± 6.42 among Chinese college students during the pandemic. After controlling for covariates, students in urban areas (AOR = 0.73, 95% CI = 0.61–0.87), with good family economic levels (AOR = 0.77, 95% CI = 0.66–0.91), and having psychological counseling (AOR = 0.55, 95% CI = 0.42–0.73) were positively associated with depression symptoms; meanwhile, higher anxiety symptoms were observed among medical students (AOR = 0.81, 95% CI = 0.69–0.95). Besides, healthy lifestyle such as regular physical activity and diet was associated with depression and anxiety symptoms. Multiple linear models revealed that medical students (β = 0.479, P = 0.031), those with good family economic level by self-evaluation (β = 1.283, P < 0.001 for good; β = 3.013, P < 0.001 for general), good academic performance by self-evaluation (β = 1.786, P < 0.001 for good; β = 3.386, P < 0.001 for general), learning burden (β = 1.607, P < 0.001 for general; β = 2.117, P < 0.001 for light), regular physical activity (β = 0.859, P < 0.001), daily routine (β = 1.289, P < 0.001), diet (β = 1.714, P < 0.001), and sufficient sleep (β = 1.408, P < 0.001) had more score of SWLS (all β > 0, P < 0.05), while senior students (β = −1.053, P=0.009), students having psychological counseling (β = −1.753, P < 0.001), and drinking (β = −0.743, P = 0.012) had lower satisfaction with life. Conclusions These findings suggest that more attention should be paid to psychological health among college students, especially during and after the COVID-19 outbreak. Policy makers and educators should help college students develop a healthy lifestyle with regular diet and exercise to promote the psychological health of college students.